Analisis Kepuasan Pengunjung terhadap Pelayanan Wisata dengan Menggunakan Algoritma C4.5 di Lanakila, Bendungan Way Sekampung - Fitria Yulia, Aviv; Wasalan, Ahlan; Herdian Andika, Tahta (Jurnal Rekayasa Perangkat Lunak, 2025)
The tourism industry's share of regional assets consists of tourist destinations that thelocals want to visit and that have the ability to make money and advance the growth of the area. Itis imperative that the quality of tourism services be preserved and enhanced. Positive remarks andrecommendations for the location are common among contented tourists. On the other hand,unhappy tourists may harm the reputation of the place and the travel sector as a whole.The research objective was to analyze visitor-level satisfaction with tourism services in Lanakilausing the C4.5 algorithm and identify the factors that most influence visitorsatisfaction. The C4.5 algorithm successfully built a prediction model to identify potentiallydissatisfied visitors.100 respondents completed the questionnaire that the researcher successfully distributed, and theaccuracy of the C4.5 model was 100.00%. Information service, staff attitude, food and beverage,and support were the four primary elements that were shown to have an impact on satisfaction,according to the analysis. With 100.00% accuracy, each of these categories was met